Providing Quality Pharmacy Services: Good Intentions Are Not Enough - GORECKI, PAUL (ESRI, 2010)
Elected representatives, like consumers, want reliable good quality medical services. Pharmacy services are no exception. Providing sound advice on which drug to take for a minor ailment, or the common side effects of a drug or keeping careful track of a consumer?s drug regimen, promote good health outcomes.
PUBLISHED
Dublin
ESRI Research Bulletin 2010/03/05
Keywords: Social Policy; Pharmacy Services